Market regulation and competition; law in conflict: A view from Ireland, implications of the Panda judgment - Philip Andrews; Paul K. Gorecki (The Economic and Social Research Institute (ESRI), 2010)
On 21 December 2009 the Irish High Court found that a regulatory proposal, the Variation, by the four Dublin local authorities, is a breach of national competition law. The Variation allows a single operator to collect household waste, irrespective of whether the operator is selected by competitive tender or the local authority reserves the collection function to itself. The judgment has important, possibly groundbreaking, implications. Local government is held to be an undertaking and hence its decisions susceptible to review and prohibition under national competition rules. The burden of the paper is, however, that the local authorities are not undertakings for the purposes of competition law when they made the Variation. Even if the local authorities were undertakings in this regard, competitive tendering for selecting a single operator to collect household waste collection is neither an anti-competitive agreement nor an abuse of a dominant position. If, however, the High Court judgment is affirmed by the Supreme Court on appeal, then the wider implications of the judgment will need to be explored.
Keywords: 330; competition policy; regulation; geographic market definition; abuse of dominance; collective dominance; household waste collection; definition of an undertaking; anticompetitive agreement; Article 86; Competition Act 2002; Waste Management Acts; 1996-2007; Wettbewerbsrecht; Regulierung; Abfallpolitik; Kommunalverwaltung; Irland